Establishment of The Cyber Diplomacy Toolbox (CDT) as a Joint Diplomatic Response to the European Union Against the Threat of Cyber Attack activity - Miftahul Khausar; Abdul Rivai Ras (UIN Sunan Gunung Djati, 2023)
In June 2017, the European Union increased its vigilance regarding Cyber Attack/Cybercrime issues by deciding and supporting the establishment of a framework for EU joint diplomacy on cyber threat issues, called “The EU Cyber Diplomacy Toolbox (CDT) because the cyber threat has harmed its member countries. Therefore, this study will analyze the European Union's Cyber Security strategy, especially looking at the Formation of CDT as a Joint Diplomatic Response of the European Union against the threat of Cyber Attack activity. The research method used in this study is a qualitative method using primary data sources obtained directly from the official website of the European Union and secondary data in the form of literature review. This research is analyzed using International Security Theory and Cyber Diplomacy Concepts.